2002
DOI: 10.1007/s10152-002-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of metallothionein from the digestive gland of naturally occurring and cadmium-exposed mussels, Mytilus galloprovincialis

Abstract: Polymorphism of metallothioneins in the digestive gland of naturally occurring (control) and experimentally Cd-exposed mussels Mytilus galloprovincialis (200 µg Cd l -1 ; 14 days) was studied by applying the conventional methods of Sephadex column liquid chromatography , and by an electrochemical method (DPASV) for determination of Cd, Zn and Cu concentrations in chromatographic fractions. In both control and Cd-exposed mussels, two distinct molecular mass components of the metallothioneins, monomeric (MT-10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The level of MT in ME was increased previously by exposure to cadmium or mercury, and two isoforms of apparent molecular weight 12 kDa (MT‐10) and 20 kDa (MT‐20) were isolated by polyacrylamide gel electrophoresis . Here, MTs were induced at Hg(NO 3 ) 2 concentration (100 μg Hg II L −1 or 0.1 ppm Hg) and exposure time (9 days) broadly similar to those in previous HgCl 2 (0.01 to 0.04 ppm for up to 21 days) and CdCl 2 experiments (0.1 ppm for 11 days, 0.1 ppm for 3–4 months, 0.2 ppm for 14 days, 0.2 ppm for 3–4 months, and 0.4 ppm for 22 days) and extracted by thermal denaturation (see the Experimental Section).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The level of MT in ME was increased previously by exposure to cadmium or mercury, and two isoforms of apparent molecular weight 12 kDa (MT‐10) and 20 kDa (MT‐20) were isolated by polyacrylamide gel electrophoresis . Here, MTs were induced at Hg(NO 3 ) 2 concentration (100 μg Hg II L −1 or 0.1 ppm Hg) and exposure time (9 days) broadly similar to those in previous HgCl 2 (0.01 to 0.04 ppm for up to 21 days) and CdCl 2 experiments (0.1 ppm for 11 days, 0.1 ppm for 3–4 months, 0.2 ppm for 14 days, 0.2 ppm for 3–4 months, and 0.4 ppm for 22 days) and extracted by thermal denaturation (see the Experimental Section).…”
Section: Introductionsupporting
confidence: 85%
“…The Hg:Cu:Zn molar stoichiometry, as determined from elemental analysis of the MT extracts using inductively coupled plasma mass spectrometry (ICP‐MS), is 0:1:1 in the control and 2:2:5 in the Hg mussels. The constitutive levels of Cu and Zn in naturally occurring MTs are consistent with previous observations and with the role of MTs in the intracellular homeostasis of the two essential metals . The total number of metals bound per molecule of MT was calculated by dividing the sum of the metals concentration in the MT extracts by the weight concentration of MTs in the same extracts and taking a MT‐10 molecular weight of 7.24 kDa .…”
Section: Resultsmentioning
confidence: 99%
“…In Mytilidae, MT dimers are transcriptionally induced from DNA following specific exposure to Cd(II), not to Zn(II) nor Cu(I), and are enriched in Cd relative to the monomeric form. [118][119][120][121][122][123] We conclude from this that the -HgSNP-type structure identified by HR-XANES could be a mercury-cysteinate cluster of approximate stoichiometry Hg7Cys16.…”
Section: Mercury-cysteinate Clustersmentioning
confidence: 70%
“…For the remaining peaks, their elution times and shapes remained comparable to those of the controls. Ivankovic et al [33] showed that MT-20 was primarily induced in Mytilus galloprovincialis after Cd exposure and represented a Cd-induced form of MT. Two molecular size classes of MT (MT-10 and MT-20) [16,31] have been suggested to play different roles in metabolism and detoxification of metals [32].…”
Section: Separation Of Metal-binding Protein Ligands Using Hplcmentioning
confidence: 99%